A Specific β-Glucosidase-Aggregating Factor Is Responsible for the β-Glucosidase Null Phenotype in Maize - Esen, Asim (American Society of Plant Physiologists, 2000)
Maize (Zea mays L.) β-glucosidase was extracted from shoots of a wild-type (K55) and a “null” (H95) maize genotype. Enzyme activity assays and electrophoretic data showed that extracts from the null genotype had about 10% of the activity present in the normal genotype. Zymograms of the null genotype were devoid of any activity bands in the resolving gel, but had a smeared zone of activity in the stacking gel after native polyacrylamide gel electrophoresis. When extracts were made with buffers containing 0.5% to 2% sodium dodecyl sulfate, the smeared activity zone entered the resolving gel as a distinct band. These data indicated that the null genotypes have β-glucosidase activity, but the enzyme occurs as insoluble or poorly soluble large quaternary complexes mediated by a β-glucosidase-aggregating factor (BGAF). BGAF is a 35-kD protein and binds specifically to β-glucosidase and renders it insoluble during extraction. BGAF also precipitates β-glucosidase that is added exogenously to supernatant fluids of the null tissue extracts. The specific β-glucosidase-aggregating activity of BGAF is unequivocally demonstrated. These data clearly show that the monogenic inheritance reported for the null alleles at the β-glucosidase gene is actually for the BGAF protein, and BGAF is solely responsible for β-glucosidase aggregation and insolubility and, thus, the apparent null phenotype.